Efficacy of wearable devices detecting pulmonary congestion in heart failure: a systematic review and meta-analysis - Murray, Cian P.; Kenny, Andrew P.; O’Sullivan, Niall J.; Murphy, Ross T.; Curtain, James P. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHeart failure (HF) hospitalizations are prognostically significant. Implantable hemodynamic monitors detect early congestion but are invasive and costly, with no clear mortality benefit. Wearable devices offer a non-invasive alternative for monitoring congestion. This meta-analysis examines the efficacy of wearable devices in reducing HF hospitalizations and mortality compared to standard care.MethodsA systematic review and meta-analysis were conducted following PRISMA guidelines. PubMed, EMBASE, MEDLINE, and Cochrane databases were searched for trials comparing wearable device-guided care with standard HF treatment. Outcomes included hospitalisation for HF, worsening HF events (hospitalisation or emergency department visit for HF) and all-cause mortality. Total (first and recurrent) event meta-analyses were performed using random effect models.ResultsFour studies met inclusion criteria, including 958 patients who were enrolled either at the time of or within 10 days of discharge from a hospitalization for HF. Wearable device-guided care resulted in a 41% reduction in hospitalisations for HF (RR: 0.59, 95% CI: 0.41–0.87, p = 0.007) and a 40% reduction in HF events (RR: 0.60, 95% CI: 0.42–0.86, p = 0.005) compared to standard care. All-cause mortality was reduced by 26% in the wearable monitoring arm (RR: 0.74, 95% CI: 0.55–0.99, p = 0.04). The composite outcome of HF hospitalization and mortality was 37% lower with wearable monitoring (RR: 0.63, 95% CI: 0.44–0.91, p = 0.04). Treatment for HF, guided by wearable devices that measure pulmonary congestion, reduced hospitalisations for HF and all-cause mortality in recently hospitalised patients.ConclusionWearable devices are a promising non-invasive strategy for managing high-risk patients, particularly when transitioning care from acute to community settings..Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024607770, identifier PROSPERO CRD42024607770.